Back Cover. Issue 5 (1st February 2023) - Unknown
Abstract : Proteus mirabilis and Proteus vulgaris are zoonotic pathogens which can cause public health disease. Owing to their antibiotic‐resistance, developing vaccines against these pathogens is urgently required. Herein, we describe the first synthesis of the common O‐antigen (trisaccharide to nonasaccharide) of Proteus mirabilis OE and Proteus vulgaris TG 103. Two challenging 1, 2‐ cis ‐glycosidic bonds were successfully constructed by use of conformation‐restrained donors under bifunctional organothiourea catalysis or gold(I) catalysis. A primary immunological evaluation was carried out and the results revealed that the synthetic common O‐antigens both hexasaccharide and nonasaccharide can strongly bind with the IgG antibodies in the sera. More details are discussed in the article by Zhang et al . on page 535—543. Abstract : Proteus mirabilis and Proteus vulgaris are zoonotic pathogens which can cause public health disease. Owing to their antibiotic‐resistance, developing vaccines against these pathogens is urgently required. Herein, we describe the first synthesis of the common O‐antigen (trisaccharide to nonasaccharide) of Proteus mirabilis OE and Proteus vulgaris TG 103. Two challenging 1, 2‐ cis ‐glycosidic bonds were successfully constructed by use of conformation‐restrained donors under bifunctional organothiourea catalysis or gold(I) catalysis. A primary immunological evaluation was carried out and the results revealed that the synthetic common O‐antigens both hexasaccharide and nonasaccharide can strongly bind with the IgG antibodies in the sera. More details are discussed in the article by Zhang et al . on page 535—543.